Why you must know this man : the life and times of Amit Dutta Gupta - Malhotra, Arjun; Sengupta, Sushmita (Response business books., 2015)
"The tale of the IT revolution in India told through the life of one of its stimulators--Amit Dutta Gupta."--Back cover